Regulasi dan Represif Produktivitas Ilegal Ciu Bekonang, 1920 - Yayang Novita Ardhaneswara; Tri Yuniyanto (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
The Dutch East Indies government implemented policies to regulate the production of alcoholic beverages in Indonesia by enforcing regulations and cracking down on locally produced alcohol. The production and distribution of alcoholic beverages were governed by customs regulations, monopolies, and a licensing system aimed at increasing state revenue while also controlling societal morals and social norms. These policies impacted traditional ciu bekonang producers, who generally lacked official permits, resulting in their activities being classified as illegal distillation. Consequently, many producers resorted to clandestine distillation to evade colonial authorities’ oversight. The colonial government subsequently responded to this situation by implementing administrative regulations, surveillance, and repressive measures against producers engaged in illegal distillation. The objective of this study is to examine how the Dutch East Indies colonial government implemented regulations and repressive measures regarding alcoholic beverages, particularly the traditional ciu bekonang. The research employs a historical methodology. The results of the study indicate that the production process for ciu bekonang required low production costs and offered relatively high profit potential. Recognizing this profit opportunity, the Dutch East Indies colonial government subsequently implemented policies regarding alcoholic beverages to regulate production and boost the economy. These regulations impacted ciu bekonang distilleries, which the colonial government considered illegal because they lacked distillation permits. The Dutch East Indies colonial government enforced these regulations to crack down on the production of illegal ciu bekonang distilleries by conducting raids, seizures, and arrests of producers by the Surakarta city police.